2000
DOI: 10.1590/s0004-282x2000000200001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in mesial temporal lobe epilepsy surgery

Abstract: -Eighty-four patients submitted to anterior temporal lobectomy were evaluated retrospectively in order to correlate the different type of simple partial seizure (SPS) and their prognostic implications in patients with mesial temporal sclerosis. The patients were divided in two groups following the classification of Engel; Group 1 (53 patients) included patients Class I (without seizures or of good outcome) and Group 2 (31 patients) included Classes II, III and IV (with seizures or of bad outcome). The two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…1). This suggestion is in agreement with findings in several studies in intellectually unselected groups of patients (48–52). However, some studies failed to find a relation between duration of epilepsy and outcome (53–56).…”
Section: Discussionsupporting
confidence: 93%
“…1). This suggestion is in agreement with findings in several studies in intellectually unselected groups of patients (48–52). However, some studies failed to find a relation between duration of epilepsy and outcome (53–56).…”
Section: Discussionsupporting
confidence: 93%
“…While unilateral hippocampal atrophy is indicator of good surgical prognosis in patients with temporal lobe epilepsy, some patients do not become seizure free after surgery (Berkovic et al, 1995;Prevedello et al, 2000). Our post-operative MRI analysis might help assess a possible role for remaining TPC, EC, PRC and PHC in recurrent seizures.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, Sirven et al 21 studied a large number of patients undergoing temporal lobectomy and observed that patients younger than 50 years had a higher likelihood of seizure freedom compared with those older than 50 years, although the procedure was considered safe and beneficial in both groups. Conversely, a Brazilian investigation reported no statistical difference of age at surgery with regard to postsurgical outcome after temporal lobectomy 22 . We did not observe a statistical difference regarding outcomes between patients younger and older than 50 years at the time of surgery (Table 5); the procedure proved to be safe and beneficial to both groups, which is in accordance with the literature 21 .…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have observed that a longer epilepsy duration before surgical treatment predicted worse seizure outcome 19,22 . However, Baldauf et al did not reach those conclusions 24 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation